(untitled) (Entrepreneurship Journal for Finance and Business, 2023)
The research aims to explain the measurement and accounting disclosure of lease contracts in accordance with the IFRS 16 standard and its impact on the informational content of the financial statements. To achieve the research objective, the researcher applied the IFRS 16 standard in Gulf Bank because it did not apply the IFRS 16 standard during the period of application of the standard in 2019, and the researcher prepared The financial statements were prepared in accordance with the requirements of the standard before and after application, and in a retrospective manner, according to what the standard allowed, with other variables held constant. The researcher provided a detailed analysis of the impact of applying IFRS 16 on the informational content of the financial statements by comparing the results before and after application, as well as the impact of that application on Financial ratios. The researcher reached a set of conclusions, the most important of which are the following: - The application of the IFRS 16 standard leads to the recognition of the right to use the asset among non-current assets, which leads to an increase in assets with a decrease in prepaid expenses, as a result of the amendments in order to apply the standard represented by reversing the prepaid expenses before application. In addition, recognizing lease obligations as non-current liabilities leads to an increase in total liabilities. The application of IFRS 16 affects the informational content of the statement of changes in equity, especially when applied using the modified retrospective method, as a decrease in retained earnings resulting from an increase in the volume of expenses due to an increase in debit interest expenses and depreciation expenses leads, therefore, to a decrease in retained earnings. The research concluded with a number of recommendations, the most important of which are: - The need for lease contracts to be clearer by stating the important paragraphs that have an impact on the process of accounting treatments related to the application of IFRS 16, which are (duration, payments, purchase option, the extent of the lessee’s control over the asset subject to the lease, and so on). - The necessity of qualifying staff working in accounting departments in the banking sector, given that it is obligated to apply international standards and other sectors through training on conducting accounting treatments for lease contracts in accordance with the IFRS16 standard, as treatments that are radically different from what used to be the treatment of lease contracts according to local accounting systems.